PROMOTING UNDERGRADUATE STUDENTS’ SCIENTIFIC LITERACY THROUGH A SCIENCE COMMUNICATION PROJECT - Melina Murgel; Diorleno Santos; Liliana Marzorati (Química Nova)
Misinformation is a pervasive threat to democracy, human health, the environment, and many other spheres touched by society. This raises concern about what citizens need to know so they can identify and avoid false claims, making individual and collective decisions based on evidence. Reliable scientific knowledge reaches the public through science communication. However, simply communicating ready-made claims is not enough to empower people in their daily decision-making. Aiming to contribute with possible pathways for science education for social transformation, a didactic activity in which undergraduate students designed science communication pieces was developed. It was implemented in three different undergraduate Chemistry courses, resulting in 67 science communication pieces. This study aimed to identify indications of scientific literacy in students’ productions by analyzing them for the presence of the Structural Axes of Scientific Literacy. The results showed that the majority of the pieces presented axes (1) Scientific Concepts and (3) Science, Technology, Society, and Environment (STSE), while axis (2) Nature of Science (NOS) was addressed in about one-third of them. This reinforces that epistemology of science needs to be highlighted in science education curricula and practice. Yet, based on the results, the science communication pieces complied with socially engaged scientific literacy.